Kontribusi Saung Angklung Udjo Dalam Pembentukan Karakter Anak Bangsa Melalui Kegiatan Seni Tradisional: Saung Angklung Udjo's Contribution to the Formation of the Nation's Character Through Traditional Art Activities - Agestin, Titan; Rabbani, Faris; Haiki, Much Ahsan; Azzahra, Mayra Havi; Clarentiyas, Maria Renata; Silalahi, Christina Adilla; Wilodati, Wilodati; Supriyono, Supriyono (DAS Institute, 2025)
Children’s character development cannot rely solely on formal education, it also requires direct cultural and social experiences. Saung Angklung Udjo (SAU) serves as a nonformal learning environment where traditional arts and character education are integrated. This study aims to analyze the role of SAU in strengthening character education through traditional art activities. A qualitative descriptive approach was employed, with data collected through participant observation, in-depth interviews with managers, instructors, and child participants, as well as documentation review. The findings reveal that angklung training and performances foster discipline through routine practice, teamwork through coordinated group performance, responsibility, tolerance, and cultural awareness. Group musical interaction also encourages mutual respect and appreciation of diversity. These results indicate that SAU plays a dual role in preserving Sundanese cultural heritage and nurturing the character of younger generations. Traditional arts are proven to be an effective medium for internalizing moral values in a natural and participatory manner.